(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
Luisa Capetillo and Salvadora Onrubia de Botana were anarchist militants in the early 20th century, from Puerto Rico and Argentina respectively. They have a series of common characteristics. Both of them are a real anarcho feminism icon developed along with other manifestations of the 1920 vanguard. They were journalists, writers, and militants. Also, they were the first women play writers in Latin America producing a feminist theater truly revolutionary. The unity of their themes shows the existence of an anarcho feminist intertextuality between the Americas.